Mom and Dad for students in Residential College - UMP, PNC (2020)
In addition to the sacrifice of health and safety officers to go on duty as frontliners during the Movement Control Order (MCO) to curb the Covid‐19 outbreak, the role of principals and fellows of residential colleges is also crucial in ensuring the safety and wellbeing of the students who stay on campus.